2017
DOI: 10.1007/s00122-017-2909-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping identifies CsGCN5 encoding a histone acetyltransferase as putative candidate gene for tendril-less1 mutation (td-1) in cucumber

Abstract: Next-generation sequencing-aided map-based cloning delimited the cucumber tendril - less1 ( td - 1 ) locus into a 190.7-kb region in chromosome 6 harboring a putative, novel-function candidate gene encoding a histone acetyltransferase ( CsGCN5 ). The tendril initiated from the lateral meristem is an important and characteristic organ for the species in the Cucurbitaceae family including cucumber (Cucumis sativus L.). While the tendril has its evolutionary significance, it also poses a nuisance in cucumber cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Furthermore, A. thaliana AtGCN5 is involved in light‐activated expression of many genes (Li et al ., ). Cucumber CsGCN5 mutants, besides displaying the tendril‐less phenotype, display defects in development similar to A. thaliana AtGCN5 mutants, which suggests that CsGCN5 may play similar roles during cucumber development as in A. thaliana (Chen et al ., ). Hence, CsGCN5 might be involved in light signaling during tendril development in cucumber, being somehow associated with the skototropic behavior of tendrils in this plant.…”
Section: Molecular Control Of Shoot‐derived Tendrils In Cucurbitaceaementioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, A. thaliana AtGCN5 is involved in light‐activated expression of many genes (Li et al ., ). Cucumber CsGCN5 mutants, besides displaying the tendril‐less phenotype, display defects in development similar to A. thaliana AtGCN5 mutants, which suggests that CsGCN5 may play similar roles during cucumber development as in A. thaliana (Chen et al ., ). Hence, CsGCN5 might be involved in light signaling during tendril development in cucumber, being somehow associated with the skototropic behavior of tendrils in this plant.…”
Section: Molecular Control Of Shoot‐derived Tendrils In Cucurbitaceaementioning
confidence: 97%
“…In addition, Mizuno et al (2015) identified a serine residue in the DNA-binding region of the protein that may also have functional significance for tendril evolution in Cucurbitaceae and is unique to C. sativus, C. melo and Citrullus lanatus. Recently, tendril-less1 (td-1), another C. sativus tendril-less mutant has been described (Chen et al, 2017). Tendril-less1 phenotype is caused by a nonsynonymous single nucleotide polymorphism (SNP) in the first exon of the gene CsGCN5 (C. sativus GENERAL CONTROL NONDEREPRESSIBLE 5; Chen et al, 2017).…”
Section: Molecular Control Of Shoot-derived Tendrils In Cucurbitaceaementioning
confidence: 99%
See 2 more Smart Citations
“…The higher observed relative transcript abundance of all BdGCN5 variants in crown tissue, when compared to aerial tissues, suggests a putative role in meristem-dependent processes (Figures 2D–F ). This observation is not surprising as GCN5 is known to be involved in developmental mechanisms in other plant species (Bertrand et al, 2003 ; Vlachonasios et al, 2003 ; Cohen et al, 2009 ; Kornet and Scheres, 2009 ; Poulios and Vlachonasios, 2016 ; Chen et al, 2017 ). Following exposure to low temperatures, the apparent circadian increase in gene expression is repressed in all BdGCN5 alternative transcripts (Figure 3A ).…”
Section: Discussionmentioning
confidence: 91%